Optimasi Branding Produk UMKM dan Peningkatan Popularitas Hutan Telagasari Sebagai Destinasi Wisata Lebah Madu di Kota Balikpapan - Rifqiandi, Muhammad; Harli Andrika Lomo; Muhammad Noor Ihsan Fadhilah; Amalia Kartika; Rangga Hermawa; Paulus Anthony Zejlstra; Desilya Lau; Mujahidin, Syamsul; Tama, Yanuar Bhakti Wira (LOSARI DIGITAL, 2025)
Telagasari Urban Forest, as a unique kerangas forest ecosystem in Kalimantan, holds significant potential in economic, ecological, and social aspects through sustainable management and honey bee cultivation. However, limited digital promotion constrains the utilization of this potential. A community engagement program in RT 45, Telagasari, Balikpapan, aimed to enhance the digital marketing skills of local MSMEs and develop the educational tourism site